Scabies of Animals and Humans: Problems and Control Strategy - Tolibin Iskandar (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2000)
Scabies is a contagious skin disease caused by Sarcoptes scabiei affecting a wide range of host species including buffalo, pigs, goats, horses, rabbits, dogs, cats, and humans. The disease in livestock causes skin irritation, decreases of meat production and quality of skin as well as affecting human health. Scabies has a worldwide distribution, including Indonesia with various prevalence, morbidity, and mortality in different host species. Diagnostic of the disease is carried out by observing clinical symptoms and scraping the infected skin to find the parasite. Scabies can be prevented by good sanitation, and chemotherapy of livestock is performed by ivermectine, asuntol and neguvon injections.   Key words : Scabies, animals, humans, diagnostic, control